Effect of Empty Bunch Fruits Biochar for Growth of Pakcoy (Brassica rapa) in Heavy Metals Contaminated Soil - Arvamusa, Mevlana; Radjamin, Irviano Panusunan; Juliastuti, Sri Rachmania; Darmawan, Raden; Fahmi, Fahmi; Meka, Wahyu; Rachmaniah, Orchidea (Journal of Fundamentals and Applications of Chemical Engineering, 2023)
Production of Crude Palm Oil (CPO) generates waste, one of which is Empty Fruit Bunch (EFB). EFB has a high potential for further utilization due to its carbon and nitrogen content. The abundant carbon content can be utilized and further processed into a value-added product such as biochar. This study aims to investigate the influence of waste mixtures from various parts of the oil palm and the effect of temperature in furnace pyrolysis and microwave pyrolysis methods on biochar production for remediating and reducing heavy metal pollution in soil. The preparation of oil palm waste materials consists of EFB, trunks, and oil palm shells, which are then crushed and refined. Through proximate and ultimate testing, two parts of oil palm waste with the highest carbon content were obtained and used in biochar production with a waste ratio of 80:20. Biochar production was carried out using the furnace pyrolysis method at temperatures of 200, 300, and 400°C for 3 hours. The biochar was added to soil media planted with Pakcoy (Brassica rapa). The effectiveness of biochar in the remediation of heavy metal pollution in soil was analyzed